Menumbuhkan Pendidikan Karakter Masyarakat Tangki Dahuyan Melalui Sosialisasi dan Pembuatan Tempat Sampah - Merilyn Merilyn; Igo Aditia Putra; Roron Roron; Dian Adriana Agnes Hamong; Eni Eni; Kristria Nindi; Dhea Agustina Hawini; Lisa Florence Esuru; Nina Jesika; Rada Christina; Restani Varonika; Rinie Rinie; Ribka Filistina; Rona Siska; Salini Salini; Krisdayanti Krisdayanti; Saika Eklesiasi (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
Character education is very important in shaping people's attitudes and behaviors. This research aims to develop character education in Dahuyan Tank Village through socialization activities and making garbage cans. A qualitative method with a descriptive approach is used to understand how this program affects environmental awareness and social values of the community. The results of this study show that socialization accompanied by the creation of garbage cans can increase community awareness and responsibility for the environment, as well as instill values such as cooperation, discipline, and responsibility.